2018
DOI: 10.3390/nu10091143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tempeh Fermentation with Lactobacillus plantarum and Rhizopus oligosporus on Streptozotocin-Induced Type II Diabetes Mellitus in Rats

Abstract: The increased consumption of high fat-containing foods has been linked to the prevalence of obesity and abnormal metabolic syndromes. Rhizopus oligosporus, a fungus in the family Mucoraceae, is widely used as a starter for homemade tempeh. Although R. oligosporus can prevent the growth of other microorganisms, it grows well with lactic acid bacteria (LAB). Lactobacillus plantarum can produce β-glucosidase, which catalyzes the hydrolysis of glucoside isoflavones into aglycones (with greater bioavailability). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 81 publications
(88 reference statements)
3
28
0
1
Order By: Relevance
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to several previously published studies, fermented foods have beneficial effects on the gastrointestinal tract system. Moreover, recent studies have shown that supplementation of fermented foods had beneficial effects in improving symptoms of type 2 diabetes mellitus, impaired glucose metabolism, obesity, irritable bowel syndrome, hyperlipidemia, hypertension and osteoporosis [2,3,7,[51][52][53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidative compounds are also produced during fermentation [58]. Fermented soybean is incubated with Aspergillus oryzae, Bacillus subtilis and Rhizopus oligosporus, and it has a higher degree of anti-lipid peroxidative effects compared with steam soybeans [56,59,60]. Its active constituents include free isoflavones, such as daidzein and genistein, which are considered major antioxidants [61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…The results of many other animal studies indicate that supplementation with probiotic Lactobacillus spp. bacteria induced SCFAs production by modulation of the intestinal microbiome [14,84,115,116]. For example, the probiotic bacteria Bifidobacterium pseudocatenulatum CECT 7765 administered to rats that received high-fat diets had an effect on increasing the intestinal barrier function, reducing endotoxemia and accelerating metabolism [117,118].…”
Section: Obesitymentioning
confidence: 99%
“…Gut microbiota also produces short-chain fatty acids (SCFAs) which regulate intestinal barrier integrity and immune homeostasis [25]. In human and animal studies, the SCFA levels were found to be decreased with an imbalance in gut microbiota, affecting immune homeostasis [3,26,27]. Hence, for healthy aging the maintenance of proper microbial populations of caecal and mucosal sites is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are living microbes that, when administered in adequate amounts, confer health benefits on the host [5,14]. In a variety of animal models, treatment with probiotics containing lactic acid bacteria (LAB) have been reported to modulate the gut microbiota, SCFA production and inflammatory responses [6,21,27]. Previously, we have reported that L. acidophilus DDS-1, a clinically-documented probiotic strain [28,29,30,31], was able to improve the metabolic phenotype via modulating faecal microbiota composition in aging mice [6].…”
Section: Introductionmentioning
confidence: 99%